Identifying and addressing challenges in teaching English at SDN Mangunsari - Ibrahim, Nuno Heydie; Nuratika, Fauziah Diah; Fortinasari, Paulina Besty (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
English language teaching in primary schools provides an important basis for students’ language development. The development of English language skills in elementary school students is important. The primary goal of this study was to explore the challenges that teachers face when teaching English at SDN Mangunsari. The qualitative method was used in this study to identify and classify the specifics of challenges in teaching English. The researchers gather the data through a observation to identify and address challenges faced by teachers when teaching English at SDN Mangunsari. The collected data will be analyzed using the descriptive analysis method. The difficulties in teaching English at SDN Mangunsari include curriculum transitions, gaps generated by students of different ages within the same grade, and inconsistency caused by a lack of alignment between teaching and assessment. To overcome the challenges found at SDN Mangunsari when teaching English, transition English classes, cooperative learning, and consistent English teaching in all grades must be implemented. These strategies attempt to create a suitable learning environment and to make the English language topic more accessible at SDN Mangunsari.